The role of end-of-life palliative sedation: medical and ethical aspects - Review - Menezes,Miriam S. (2019)
Abstract Background and objective: Palliative sedation is a medical procedure that has been used for more than 25 years to relieve refractory symptoms not responsive to any previous treatment in patients with no possibility of cure and near the end of life. Many uncertainties persist on the theme regarding definition, indications, decision making, most appropriate place to perform the procedure, most used drugs, need for monitoring, fluids and nutritional support, and possible ethical dilemmas. The objective of this review was to seek a probable consensus among the authors regarding these topics not yet fully defined. Method: An exploratory search was made in secondary sources, from 1990 to 2016, regarding palliative sedation and its clinical and bioethical implications. Conclusions: Palliative sedation is an alternative to alleviate end-of-life patient suffering due to refractory symptoms, particularly dyspnea and delirium, after all other treatment options have been exhausted. Decision making involves prior explanations, discussions and agreement of the team, patient, and/or family members. It can be performed in general hospital units, hospices and even at home. Midazolam is the most indicated drug, and neuroleptics may also be required in the presence of delirium. These patients' monitoring is limited to comfort observation, relief of symptoms, and presence of adverse effects. There is no consensus on whether or not to suspend fluid and nutritional support, and the decision must be made with family members. From the bioethical standpoint, the great majority of authors are based on intention and proportionality to distinguish between palliative sedation, euthanasia, or assisted suicide.